Perancangan Interior Restoran All You Can Eat Jepang di Surabaya - Andereas Pandu Setiawan, David Fandi Wahjoedin (Intra, 2014)
Surabaya as a growing city, has a lot of potential in the field of culinary, culinary either local to foreign countries, especially among young people. this is a great attraction for the investors to make a restaurant or cafe - cafe which has a unique atmosphere and attract people, especially among the young. Here is Interior Design has the opportunity to create a restaurant or cafe interior attractive interest by the public, especially among the young.Â